PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT SURYA MADISTRINDO TBK KARAWANG - Utami Madya Ayu Nabila (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine, analyze and explain whether compensation and job satisfaction have a partial or simultaneous effect on employee performance at PT Surya Madistrindo TBK Karawang. This study uses quantitative methods of descriptive analysis and verification, namely collecting, presenting, analyzing, testing hypotheses, providing conclusions and suggestions. The sample in this study used a non-probability sampling technique with an incidental sample method of 107 people using a Likert scale technique and path analysis. The results showed that compensation and job satisfaction on employee performance obtained an average of 391.1, 388.0 and 384.8, meaning that all of these variables were considered good. The correlation coefficient between Compensation and Job Satisfaction obtained a value of 0.995, which means that the correlation is strong, positive and significant. The partial effect of compensation on employee performance gets a value of 42.0% while job satisfaction on employee performance has a greater value of 56.4%. The simultaneous effect of Compensation and Job Satisfaction on Employee Performance obtained a value of 98.3%, the remaining 17% was influenced by other variables that were not studied.